USING REMOTE CAMERAS FOR POPULATION ESTIMATION OF GOULD'S TURKEYS IN SOUTHEASTERN ARIZONA - Shelli A. Dubay; Brian F. Wakeling; Timothy D. Rogers; Susan R. Boe; Michael J. Rabe (Wildlife Society Bulletin)
Abstract: We evaluated population estimation techniques for Gould's turkeys (Meleagris gallopavo mexicana) in southeastern Arizona. The Huachuca Mountain population of Gould's turkeys could be used as a source to further restoration efforts, but due to its unknown population size, we had concerns regarding overexploiting a limited population. Because these turkeys are limited in range within the United States and occupy isolated mountain ranges in Arizona (i.e., closed population), these Gould's turkeys provide a unique opportunity to compare and contrast techniques for estimating population size. Our study population in the Huachuca Mountains, Arizona, was reestablished following extirpation with the release of 9 and 12 turkeys in 1983 and 1987, respectively. We baited and trapped Gould's turkeys during winter 2000, 2001, and 2002 and affixed each bird with a radiotag and patagial wing markers. We used photographs taken with remotely activated cameras in 5 canyons in March and April 2002 as remarks. We used the joint hypergeometric maximum likelihood estimator from the NOREMARK computer program to estimate population size using number of known marked birds in the population and number of marked and unmarked birds photographed during each sampling period. We then extrapolated this estimate from 5 canyons to the entire mountain range and compared this estimate to that from a walking survey. Estimates included 84 (95% CI = 80–91) for the area within the 5 canyons sampled, 286 (range = 272–306) when the estimate was extrapolated to the entire mountain range, and 203 (range = 110–296) for the ground survey. The photographic technique yielded more precise estimates than the ground survey, but the photographic method required approximately twice as many hours to conduct. Decisions on methods selected for future surveys should be based on management requirements.